Revegetation to slow buckthorn reinvasion: strengths and limits of evaluating management techniques retrospectively. Issue 1 (16th November 2020) - Wragg, Peter D.; Schuster, Michael J.; Roth, Alexander M.; Bockenstedt, Paul; Frelich, Lee E.; Reich, Peter B.
Abstract : Understanding the long‐term success of ecosystem restoration following invasive plant removal is challenging. Long‐term experiments are costly and slow to yield results, while management decisions must often be made immediately. Alternatively, retrospective studies can leverage contrasting historical management strategies to provide insight into long‐term vegetation responses. We used a retrospective approach to evaluate how management techniques and site characteristics affected re‐establishment of an invasive shrub, Rhamnus cathartica (common buckthorn), in midwestern North America. Following removal, buckthorn re‐establishes rapidly from resprouts and seeds, so follow‐up control is required but often lacking. We hypothesized that revegetating using native herbaceous seed after removing buckthorn increases herbaceous cover that competitively suppresses buckthorn regeneration, to a degree. We surveyed 46 management units at 24 sites. Revegetated units had higher herbaceous cover, lower buckthorn cover, and half the ratio of buckthorn:herbaceous cover compared with unseeded units. These effects, although considerable on average, were detected against a background of high variance. Seeding increased herbaceous cover and reduced buckthorn relative abundance more strongly on less acidic, more clayey soils and where follow‐up herbicide was not applied. Additional variability in revegetation impacts may have arisen from buckthorn resprouts having a head‐start on planted seeds. Only one site had both seeded and unseeded management units. This lack of blocking—a common challenge in retrospective studies—reduced statistical power. This investigation illustrates how retrospective studies can offer relatively inexpensive first assessments of long‐term effects of management techniques; for more rigorous inference, researchers can partner with managers to conduct long‐term experiments.